INCREASING PRODUCTIVITY OF SCLUPTOR IN KAPAL VILLAGE, BADUNG, BALI (Journal of Industrial Engineering and Halal Industries, 2020)
To increase the productivity, modern hand tools such as electrical grinder, electrical drill and band saw have been used by the scluptor in Kapal village. Due to ignorance, in using them not all precaution were taken into consideration. Also squatting and bending positions produced many complaints. Therefore, an ergonomics intervention has been conducted. Using multistage random sampling technique, 20 subjects were sampled from the scluptors. Blood pressure, and heart rate were measured, and subjective feelings were recorded using Nordic Body Map, before and after working for a week. The results showed that after working; 1.2% increased in systolic blood pressure; 4.7% increased HR per minute; and 20.7% subjective complaints (p0.05). HR 4.96% (p
Keywords: productivity; sculptors